(untitled) (CAHIERS MAGELLANES-NS, 2024)
BACKGROUND: Ocular surface disorder and tear-film instability are one of the most common post-cataract surgery complications, affecting patient comfort and visual outcomes. Artificial tear substitutes like Carboxymethylcellulose (CMC) 0.5% and Polyethylene Glycol (PEG) 0.4% / Propylene Glycol (PG) 0.3% are essential for managing these conditions. OBJECTIVE: This study aims to compare the efficacy of Carboxymethylcellulose 0.5% and Polyethylene Glycol 0.4% / Propylene Glycol 0.3% as tear substitutes in managing ocular surface disorder and tear-film instability in patients following cataract surgery. MATERIALS AND METHODS: A prospective randomized comparative study was conducted in the Department of Ophthalmology, Saveetha Medical College and Hospital, Chennai. The study comprised 40 individuals who underwent cataract surgery over a period 6 months. A dry eye workup, including Schirmer's test (ST1), tear film breakup time (TBUT), and Ocular Surface Disease Index (OSDI) scoring will be carried out for all patients before and after the surgery. Patients will be separated into two groups and randomly assigned to be treated with a specific lubricant using stratified random sampling. Following cataract surgery, patients in groups 1 and 2 started receiving carboxymethyl cellulose 0.5% and polyethylene glycol 0.4%/propylene glycol 0.3%, respectively. RESULTS: The outcomes of our study demonstrate that polyethylene glycol 0.4%/propylene glycol 0.3%, is more successful in promoting tear-film stability in those who have had cataract surgery than carboxymethylcellulose 0.5%. CONCLUSION: Our results emphasize the importance of using artificial tears in patients who have undergone cataract surgery. It also demonstrates how to prevent and reduce clinical complications after the treatment. The symptomatology improved after surgery.